Artificial intelligence as augmenting automation: Implications for employment - TSCHANG, F. Ted (Institutional Knowledge at Singapore Management University, 2021)
There has been great concern in recent years that artificial intelligence (AI) may cause widespread unemployment, but proponents say that AI augments existing jobs. Both of these positions have substance, but there is a need is to articulate the mechanisms by which AI may actually do both, and in the process, transform work and business organizations alike. We use economic studies showing past transformations automation wrought on the structure of employment and skills (such as the favouring of nonroutine skills) to articulate a ground for discussion. We then use case evidence of AI and automation to show how AI is transforming automation, allowing firms to more easily monitor and control work automatically. The remaining work tends to be modularized, allowing for further replacement in the future. We also illustrate the dynamic effects that take place when AI is further combined with other key technologies, garnering for the firms economies of scale and scope. The end result tends to be employment structures favoring the highly technical occupations (illustrating how the economic findings can occur). We end with a call for more critical conversations between society and business, and introspection on what business schools should be teaching.